Evaluation of Early Marriage Prevention in Adolescent Children: A Descriptive Qualitative Study of the Implementation of Maturing Marital Age in Kotabaru, Indonesia - Amalia, Rizqi; Handayani, Lisda; Kusvitasari, Hairiana (Jurnal Kesehatan Metro Sai Wawai, 2023)
Introduction: Early marriage of girls increases the risk of death and morbidity in mothers and babies, including stunting. Several policies and programs to mature or increase the age of marriage have been implemented to eliminate this practice, but early marriages are still found. Purpose: This research examines in depth the evaluation of the implementation of the program for maturation and increasing the age of marriage for adolescent children. So, it can be identified the factors that cause teenage marriage to still be high. Method: A qualitative descriptive method was used as a research design and recruited six participants to study the maturation program and increasing the age of marriage as the main participants and triangulation participants. Participants triangulate the validity and reliability of information. Data or information collection uses interviews which are reported in the form of narrative descriptions and analyzed using an interactive analysis model for coding. Results: We found 3 research results on the reasons why there are still early marriages among adolescent children: (1) various limitations in the transformation of maturation programs and increasing the age of marriage; (1) the implementation of the program to increase the marriage age according to students has not met expectations; and (3) adolescent children who marry early are still found after graduating from school. Conclusion: The experience of adolescent children who took part in the maturation program and increasing the age of marriage felt that it did not meet expectations. Adolescent children still marry early after graduating from high school. This study indicates the need for adolescent children to receive early marriage education and its impact needs to be evaluated and improved from the input, process, and output aspects of implementing the maturation program and increasing the age of marriage so that it is attractive and meets the expectations of adolescent children.